Taxonomy development of blockchain platforms: Information systems perspectives - Sarkintudu, Shehu M.; Ibrahim, Huda; Abd Wahab, Alawiyah (IP Publishing LLC, 2018)
Blockchain platform has given information system scholars research opportunities in understanding dynamics of convergence of technology and social context. The information system research issues are complex and require taxonomies to understand the similarities and uniqueness among objects. Developing taxonomies is a complex process that needs systematic approach. This paper is a research-in-progress. We proposed taxonomy for Blockchain platform using existing method of developing taxonomies in information systems. With the unprecedented growth led to several companies to develop the varieties of Blockchain platforms. The complexity in the implementation and understanding the technical protocols leading to difficulty face by researchers and practitioners to access their full potentials. To bridge the gap, we proposed a taxonomy of Blockchains distributed ledger platforms in order to provide a mechanism for researchers and practitioners to understand the phenomenon. Final of taxonomy contains five (5) dimensions with fifteen (15) characteristics. Our analysis discovered Blockchain platforms are designed with specific goals, which prescribe its features, i.e FinTech Blockchain platforms for financial domain.